A Semantic Analysis of Snow-related Words in Danish and Kalaallisut (West Greenlandic) - Maskova, Stephanie (Scandinavian Studies in Language, 2022)
This paper emerges from the vexed question whether the allegedly many “Eskimo” terms for snow document a linkage between language, culture, and cognition. Using the semantic explication technique of the natural semantic metalanguage (NSM) approach, the emic logics embedded in the Kalaallisut snow-related words aputit and nittaappoq and the Danish snow-related words sne and det sner are unfolded. Through a comparison of the findings, the paper discusses how the physical world is conceptualized in both culture-specific and transcultural ways. The explications are based on evidence from semantic consultations and text examples. Full Text